A case of leptospirosis with acute respiratory failure and acute kidney injury treated with simultaneous extracorporeal membrane oxygenation and haemoperfusion. Issue 5 (29th May 2019) - Chavez, Joselito R; Danguilan, Romina A; Arakama, Melhatra I; Garcia, Joann Kathleen Ginete; So, Rizza; Chua, Eric
Abstract : A 47-year-old man with a recent history of wading in floodwaters presented with a 1-week history of cough, myalgia, conjunctival suffusion and decreasing urine output. The patient had uraemia, hypotension, leukocytosis, thrombocytopenia, elevated liver enzymes and oliguria. His condition quickly worsened with haemoptysis, and respiratory distress which subsequently required intubation and mechanical ventilation. Continuous renal replacement therapy was started together with haemoperfusion (HP). The patient initially required norepinephrine and this was discontinued after the first session of HP. He was referred for veno-venous extracorporeal membrane oxygenation (ECMO) due to severe hypoxia and pulmonary haemorrhage. Oxygenation and lung compliance improved, and serum creatinine levels continued to normalise with improved urine output. He was placed off ECMO, extubated and eventually discharged. Patient was diagnosed with severe leptospirosis, acute respiratory failure and acute kidney injury successfully treated with simultaneous ECMO and HP. Blood samples were positive for Leptospira spp. DNA via PCR assay.